Pengaruh Kombinasi Terapi Relaksasi Autogenik dan Musik Terhadap Tekanan Darah Warga Binaan Pemasyarakatan - Anindya Arum Cempaka; Maria Theresia Arie Lilyana (Jurnal Kesehatan Medika Udayana, 2023)
Background: Life in prison can trigger stress that affects blood pressure. One way to control blood pressure in hypertensive patients is to use non-pharmacological therapy interventions. One of them is to use autogenic relaxation and music therapy methods. Purpose: This study aimed to determine the effect of autogenic and music therapy on reducing blood pressure for inmates. Method: The research method is quasi-experimental, with one group pretest and posttest design. This research was conducted in a prison in the Surabaya area. The total sample of this study is 20 respondents. Result: After autogenic and music relaxation therapy, participants with normal blood pressure levels increased to 60%. Based on the Wilcoxon Sign Rank Test result, it's known that p-value = 0,001 with (?<0.05), which means this program may affect participants' blood pressure. Conclusion: The use of autogenic and music therapy may reduce blood pressure. This program significantly lowered participants' perception of stress, and it enhanced their perception of health